Ceremony and Popular Culture. Festivities and Objects Connected with the National Theatre and other Czech Public Buildings before 1918 - Galeta, Jan (Eikón / Imago, 2022)
The present article focuses on the festivities held between the 1860s and 1914 in the Lands of the Bohemian Crown, which were associated with various construction phases of buildings important for the Czech speaking society (especially the laying of the foundation stone and the opening ceremony). These festivities lie somewhere between the artificially constructed concepts of "high" and "low", "the elite" and "the people", and between "folk" and "mass" culture. The study aims to show that without the people, without an audience, these festivities would not be celebrations but just elite parties. Therefore, the nature of these festivals was primarily popular, as evidenced by many details, including their character, the accompanying theatre plays and souvenir items. The festivities and the whole idea of the National Theatre in Prague are examined in the first part of the article, which is followed by examples from other parts of the Czech lands and finally, medals, postcards and promotional brochures are discussed.